2021
DOI: 10.3389/fped.2021.651297
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics According to Age and Duration of Symptoms to Be Considered for Rapid Diagnosis of Pediatric Intussusception

Abstract: Purpose: The purpose of this study was to evaluate whether clinical findings in children with ileocolic intussusception differ based on age and duration of symptoms and to assess the clinical characteristics of diagnosed and undiagnosed patients to determine which symptoms make diagnosis more difficult.Methods: We reviewed 536 medical records of <15-year-old children diagnosed with ileocolic intussusception between 2008 and 2019. We divided the children into three categories according to age (<1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
25
3
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(36 citation statements)
references
References 26 publications
(32 reference statements)
7
25
3
1
Order By: Relevance
“…The findings of this study indicated that the patients follow with acute intussusception was high between July and September, which is the rainy season with a second peak in December which is the dry season in Ethiopia. The present finding was similar to the findings reported in Asia ( 20 ), Africa ( 21 ), Jimma, Ethiopia ( 22 ), and Addis Ababa, Ethiopia ( 14 ). This might be explained by the higher occurrence of preceding respiratory infections and gastroenteritis in the pediatric population during the rainy and dry seasons.…”
Section: Discussionsupporting
confidence: 92%
“…The findings of this study indicated that the patients follow with acute intussusception was high between July and September, which is the rainy season with a second peak in December which is the dry season in Ethiopia. The present finding was similar to the findings reported in Asia ( 20 ), Africa ( 21 ), Jimma, Ethiopia ( 22 ), and Addis Ababa, Ethiopia ( 14 ). This might be explained by the higher occurrence of preceding respiratory infections and gastroenteritis in the pediatric population during the rainy and dry seasons.…”
Section: Discussionsupporting
confidence: 92%
“…9.3 %). 10 Though intussusception was first described by Paul Barbette in 1692, it took over 3 centuries before its sonographic features were described in 1977. Raffainsperger has written that as far back as Hippocrates' time, there were allusions to a reduction of intussusception by the injection of air/fluid into the rectum.…”
Section: Discussionmentioning
confidence: 99%
“…Atypical presentation of intussusception in older children may explain this delayed presentation. Park et al documented the changes in clinical characteristics of intussusception in children with intussusception [14]. Poverty and a low level of awareness on the part of the parents also influence the time of presentation to the hospital.…”
Section: Discussionmentioning
confidence: 99%
“…Abdominal pain was the most common presenting symptom in the patients. Other series on intussusception also published abdominal pain as the most common symptom of intussusception [14,15]. Khasawneh et al found vomiting as the most common symptom of pediatric intussusception [11].…”
Section: Discussionmentioning
confidence: 99%